#TITLE_ALTERNATIVE# - MAHENDRATA NUGRAHA (NIM : 10208002); Pembimbing Tugas Akhir : Gunawan Handayani, MSCE, Ph.D, ARYANDI
Seismic microzonation is an activity to classify areas based on the level of the seismicity or the earthquake potential. This activity is according to the characteristic of the subsurface. The microtremor method is one of the seismic method that used for seismic microzonation. This method is using low frequency waves, so that the wavelength would be much longer than using high frequency wave. By getting the Rayleigh wave dispersion curve, then we can do the inversion to obtain the final form of the S wave velocity profile of the tested soil structure. The microtremor measurement were performed by using arrays of sensors in the form of a circle geometry or triangle geometry with a large radius. The method of the array configuration that used is Spatial Auto-Correlation (SPAC) using minimum of 4 sensors for the recording.